Effectiveness of Science Evaluation Questions on Animal Classification Material on Learning Outcomes and Problem Solving of Third Grade Elementary School Students - Esti Suciati; Elyas Djufri; Didi Supriadi (Postgraduate, University of Mataram, 2026)
This study aimed to analyze the effectiveness of third-grade elementary school science assessment questions on animal classification in measuring students’ learning outcomes and problem-solving skills. A quantitative approach with a pre-test–post-test design was employed involving 51 third-grade students. The assessment instrument consisted of science questions covering vertebrate and invertebrate classification, amphibian characteristics, and animal habitats. Data were collected through pre-test and post-test assessments and analyzed using descriptive and quantitative methods. The results indicated that the assessment questions effectively measured learning outcomes, with N-gain scores of 0.37 (moderate) in the first class and 0.25 (low) in the second class. Problem-solving analysis revealed that the first class performed better in planning solutions and drawing conclusions, while the second class showed stronger performance in understanding problems, with comparable achievement in implementing solutions. These findings demonstrate that assessment questions aligned with learning objectives and students’ cognitive development effectively evaluate both conceptual understanding and problem-solving skills. Therefore, the developed science assessment questions are appropriate as an effective evaluation tool for elementary school science learning